Study of Sustainable Tourism Development in Silokek Geopark, Sijunjung Regency, West Sumatra - Yogi Prambudi; Dyah Widiyastuti; Chafid Fandeli (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2023)
Silokek Geopark is a National Geopark located in Sijunjung Regency, West Sumatra that comprises potential attractiveness for regional as well as national tourism sector. Tourism development in Silokek Geopark has been done since 2004 in order to improve local community economy and reduce environmental degradation. Tourism development has focused on obtaining the positive impact in economic dimension and tends to ignore the sustainability of environmental and socio-cultural dimensions so far. The aims of this research are to describe changes on tourism development in Geopark Silokek as National Geopark and  to examine  sustainability of tourism development in Geopark Silokek as tourism destination. The approach used in this research is qualitative. Data were collected through observation, interviews, and document study. Collected data were analyzed by qualitative-descriptive analysis method. The result of this research showed that tourism development in Silokek Geopark as National Geopark changed to be better. The condition of tourism at the period before Silokek Geopark was legitimized as a National Geopark was not optimal while at the period after it was approved as a National Geopark the quality is getting enhancement, both in terms of attraction, amenities, accessibility, and ancillary. Furthermore, sustainable tourism development has not been implemented integrally in the development of Silokek Geopark becoming a tourism destination. The tourism development in Silokek Geopark does not show the sustainability in environmental dimension, socio-cultural dimension, nor economic dimension.